Online Car Rental System - Kumar, Deepak; Bartwal, Deepak; Gagan,; Kannan, Bharathi (Project Mentor) (IJRDO -Journal of Computer Science Engineering, 2021)
The greatest motivation behind this research is that the requisite to explore the growing popularity of web based system technology. That’s utilized by the industries to expand their services to customers this document has explained a notification based content alert for the rental systems of car so as to attenuate of consumption and time , which is favourable for letting agencies and consumers.Consequently this technique was designed automatically to sent alert SMS to consumer about the provision of restrained car. This technique is developed supported the system Life Cycle (SDLC) using the waterfall model as a technique. A user acceptance test was classified into three parts including user acceptance design, usability, case of use, include utility and alert system functions